2015
DOI: 10.3892/br.2015.498
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the impact of two types of dietary protein on brain glucose concentrations and oxidative stress in high fructose-induced metabolic syndrome rats

Abstract: Abstract. The present study explored the potential of fish proteins to counteract high glucose levels and oxidative stress induced by fructose in the brain. A total of 24 male Wistar rats consumed sardine protein or casein with or without high fructose (64%). After 2 months, brain tissue was used for analyses. The fructose rats exhibited an increase in body mass index (BMI), body weight, absolute and relative brain weights and brain glucose; however, there was a decrease in food and water intake. Fructose disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…We also demonstrated a reduction of thiol content in ST of animals exposed to HPD. Corroborating our findings, some data demonstrated that an increase of energy intake might lead to enhanced ROS in metabolically-active tissues such as the brain, causing lipid peroxidation and increased glucose oxidation (Madani et al 2015;Treviño et al 2015). It is also known that the brain uses a significant amount of oxygen and adenosine triphosphate resulting in a high susceptibility to oxidative stress (Halliwell and Gutteridge 2007).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We also demonstrated a reduction of thiol content in ST of animals exposed to HPD. Corroborating our findings, some data demonstrated that an increase of energy intake might lead to enhanced ROS in metabolically-active tissues such as the brain, causing lipid peroxidation and increased glucose oxidation (Madani et al 2015;Treviño et al 2015). It is also known that the brain uses a significant amount of oxygen and adenosine triphosphate resulting in a high susceptibility to oxidative stress (Halliwell and Gutteridge 2007).…”
Section: Discussionsupporting
confidence: 81%
“…It is known that polyphenols present in the fruits of PcRT have important antioxidant and anti-inflammatory actions (Madani et al 2015;Jayarathne et al 2017). In addition, dietary interventions with compounds such as anthocyanins and flavonoids may modulate several systems that likely improve glucose homeostasis and insulin sensitivity (Bagul et al 2012;Vendrame et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…TBARS is a marker of lipid peroxidation formed by the reaction with cytotoxic products such as malondialdehyde released during the oxidation of unsaturated fatty acids and plays an important role in the complications of MetS [43]. Lipid peroxidation induced by the consumption of HPD may be associated with increased glucose levels, which can lead to increased production of ROS by glucose autoxidation, because chronic hyperglycemia leads to the formation of end product of advanced glycation damaging cells and stimulating the production of ROS [44]. Moreover, chronic hyperglycemia present in MetS can also contribute to neuronal damage and changes in thiol groups in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cognitive and behavioral changes may occur due to oxidative stress and inflammatory cytokine release [7,10,20]. Increased oxidative stress due to high fructose uptake enhances lipid peroxidation [9]. Changes in AA and DHA metabolism, which have important roles in cell membrane integrity and fluidity, have been reported in the brain due to membrane peroxidation [7,11,21].…”
Section: Color Version Available Onlinementioning
confidence: 99%
“…Problems such as hypertension, stroke, renal insufficiency, cardiovascular morbidity, and high mortality could also develop as a result of these conditions [5,6]. In addition, several histological and clinical pathologies related to both proinflammation and increased oxidative stress in the brain have been demonstrated [7][8][9]. Cognitive decline, mood disorders, and behavioral abnormalities can develop due to increased cytokine production and brain lipid metabolism changes [7,10].…”
Section: Introductionmentioning
confidence: 99%